Clerk [videorecording (DVD)] : a documentary about Kevin Smith - Smith, Kevin, 1970-; Mosier, Scott; Affleck, Ben, 1972-; Mewes, Jason, 1974- (TCB, 2021)
A story of a man who wears many hats. All of them are backward. From award-winning filmmaker Malcolm Ingram comes an extensive all-access documentary examining the life and career of indie filmmaking icon Kevin Smith. Featuring never before seen interviews with friends, family, and filmmaking peers, along with icons of the film, comedy and comic book worlds.